A comparative assessment of vibration control capabilities of a L-shaped Gurney flap. (3rd November 2016) - Motta, V.; Quaranta, G.
ABSTRACT: This work presents the capabilities of a novel L-shaped trailing-edge Gurney flap as a device for vibration reduction. The primary effect of this L-tab is represented by a modification of the reference aerofoil mean line shape through by two counter-rotating vortical structures created at the trailing edge. The comparison of the aerodynamic loads generated by the novel L-tab Gurney flap and a classical trailing-edge flap allows to estimate the ranges of reduced frequency where the L-tab is expected to perform better than a trailing edge flap and vice versa. Linear aerostructural models for a typical section representative of a helicopter blade equipped with a partial-span L-tab or a trailing-edge flap are built, and a higher harmonic control algorithm is applied. Performance are compared between the two devices to reduce separately the N /rev harmonics of the blade root rotating frame vertical force, flapping and feathering moments. The attainment of similar results with classical trailing-edge device is a further confirmation of the potential feasibility of this novel L-tab as an effective alternative means for vibration reduction on rotor blades.